Enhancing Brain Connectivity With Infra-Low Frequency Neurofeedback During Aging: A Pilot Study - Dobrushina, Olga R.; Dobrynina, Larisa A.; Arina, Galina A.; Kremneva, Elena I.; Novikova, Evgenia S.; Gubanova, Mariia V.; Pechenkova, Ekaterina V.; Suslina, Anastasia D.; Aristova, Vlada V.; Trubitsyna, Viktoriya V.; Krotenkova, Marina V. (Frontiers in Human Neuroscience, 2022)
Aging is associated with decreased functional connectivity in the main brain networks, which can underlie changes in cognitive and emotional processing. Neurofeedback is a promising non-pharmacological approach for the enhancement of brain connectivity. Previously, we showed that a single session of infra-low frequency neurofeedback results in increased connectivity between sensory processing networks in healthy young adults. In the current pilot study, we aimed to evaluate the possibility of enhancing brain connectivity during aging with the use of infra-low frequency neurofeedback. Nine females aged 52±7 years with subclinical signs of emotional dysregulation, including anxiety, mild depression and somatoform symptoms, underwent 15 sessions of training. A resting-state functional MRI scan was acquired before and after the training. A hypothesis-free intrinsic connectivity analysis showed increased connectivity in regions in the bilateral temporal fusiform cortex, right supplementary motor area, left amygdala, left temporal pole and cerebellum. Next, a seed-to-voxel analysis for the revealed regions was performed using the post- vs. pre-neurofeedback contrast. Finally, to explore the whole network of neurofeedback-related connectivity changes, the regions revealed by the intrinsic connectivity and seed-to-voxel analyses were entered into a network-based statistical analysis. An extended network was revealed, including the temporal and occipital fusiform cortex, multiple areas from the visual cortex, the right posterior superior temporal sulcus, the amygdala, the temporal poles, the superior parietal lobule and the supplementary motor cortex. Clinically, decreases in alexithymia, depression and anxiety levels were observed. Thus, infra-low frequency neurofeedback appears to be a promising method for enhancing brain connectivity during aging, and subsequent sham-controlled studies utilizing larger samples are feasible.